Hypoxia inducible factor prolyl hydroxylases in inflammatory bowel disease - Jie Lun; Hongwei Zhang; Jing Guo; Mengchao Yu; Jing Fang (Frontiers Media S.A., 2023)
Inflammatory bowel disease (IBD) is a chronic disease that is characterized by intestinal inflammation. Epithelial damage and loss of intestinal barrier function are believed to be the hallmark pathologies of the disease. In IBD, the resident and infiltrating immune cells consume much oxygen, rendering the inflamed intestinal mucosa hypoxic. In hypoxia, the hypoxia-inducible factor (HIF) is induced to cope with the lack of oxygen and protect intestinal barrier. Protein stability of HIF is tightly controlled by prolyl hydroxylases (PHDs). Stabilization of HIF through inhibition of PHDs is appearing as a new strategy of IBD treatment. Studies have shown that PHD-targeting is beneficial to the treatment of IBD. In this Review, we summarize the current understanding of the role of HIF and PHDs in IBD and discuss the therapeutic potential of targeting PHD-HIF pathway for IBD treatment.